The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.7870/cjcmh-2009-0015
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Housing Stability for People With Serious Mental Illness

Abstract: Housing programs are complex social interventions. Research on housing for people with mental illness has proceeded without a framework for integrating emerging findings and guiding new research directions. This paper describes a definition and model of housing stability developed with stakeholders in 3 local housing systems for people with mental illness. The model describes housing stability as a dynamic relationship among 3 factors (person, housing, and support) that are influenced by broader system influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
(20 reference statements)
1
15
0
Order By: Relevance
“…We found that traditional definitions of housing stability that view material aspects of stability as the primary indicator of housing stability are insufficient to describe the experiences of these women. Similar to Sylvestre et al’s ( 2009 ) findings, our research suggests that definitions of housing stability must be broad enough to incorporate women’s lived experiences as well as their ability to be independent and exercise personal choice. Specifically, we found that for women who have left violent households, safety, security, family friendly housing, and comfort are embedded in their definitions of a stable home.…”
Section: Discussionsupporting
confidence: 80%
“…We found that traditional definitions of housing stability that view material aspects of stability as the primary indicator of housing stability are insufficient to describe the experiences of these women. Similar to Sylvestre et al’s ( 2009 ) findings, our research suggests that definitions of housing stability must be broad enough to incorporate women’s lived experiences as well as their ability to be independent and exercise personal choice. Specifically, we found that for women who have left violent households, safety, security, family friendly housing, and comfort are embedded in their definitions of a stable home.…”
Section: Discussionsupporting
confidence: 80%
“…The implicit understanding in the literature on housing stability is that it is the antithesis of homelessness and exists on a continuum (Aubry, Klodawsky, & Coulombe, ). However, as some researchers have pointed out (Brown, Ridgway, Anthony, & Rogers, ; Sylvestre, Ollenberg, & Trainor, ; Tsemberis, McHugo, Williams, Hanrahan, & Stefancic, ), definitions of homelessness and housing stability are not applied uniformly across studies, and therefore the methods used to measure these constructs differ as well. A more serious concern is that some studies in which the concept of housing stability figures prominently never actually define the term (Greene, Chambers, Masinde, & O'Brien‐Teengs, ).…”
Section: Measures and Predictors Of Stabilitymentioning
confidence: 99%
“…Work that examines the perspectives of service providers and consumers has highlighted that a house alone does not constitute housing stability and that it is not simply a question of tenure (Jakubec, Tomaszewski, Powell, & Osuji, 2012). This research emphasizes support structures that ease the transition into a mainstream life, and these supports can be seen as acting to reinforce the "housing" side of stability (see also Brueckner, Green, & Saggers, 2011;Dornbusch, 1994;Lindsey, 1995;Nemiroff, Aubry, & Klodawsky, 2010;Sylvestre et al, 2009).…”
mentioning
confidence: 99%
“…Given the ambiguity surrounding the term housing stability, Sylvestre and colleagues worked to provide a nuanced understanding of what it means (Sylvestre, Ollenberg, & Trainor, 2009). In this report, we define housing stability as going beyond solely maintaining stable housing to include access to opportunities for wellbeing (such as health professionals and recreation centres) and information (such as schools, libraries and drop-in centres).…”
Section: Literature Reviewmentioning
confidence: 99%